Profil Hasil Pemeriksaan GeneXpert Real Time Polymerase Chain Reaction (RT-PCR) Terhadap Mycobacterium tuberculosis pada Pasien Tuberkulosis Paru di Rumah Sakit Bhayangkara Polda Bengkulu Periode Januari-Desember 2018 - Sariyanti, Mardhatillah (UNIVERSITAS BENGKULU, 2021)
Background: Tuberculosis (TB) is an infection that caused by Mycobacterium tuberculosis (MTB) and the droplets can be transmitted by the air. Mycobacterium tuberculosis mainly infected the lungs, but also and infected other organs like, glands, bones, and nervous system. World Health Organization reported that there are 10 million TB cases in 2017 and 1,3 million death caused by this disease. Based on the data from Health’s Profile in Bengkulu city in 2015 there are 18.982 lung tuberculosis suspects. GeneXpert is a brand new innovation to diagnose TB based on molecular examination that uses Real Time Polymerase Chain Reaction (RT-PCR) which targeting the gene rpoB hotspot in MTB integrated and automatically processing the sample’s Deoxyribo Nucleic Acid (DNA) in disposable catridge. Method: This is an analytic description research. This research took secondary data (medical record) from the result of sputum examination by GenExpert tools from the lung tuberculosis patients at Bhayangkara Polda Bengkulu Hospital in January-December 2018 to acknowledge the result of MTB’s examination. Results: From this research, there were 150 male patients (70,1%) and 64 female patients (29,9%). The most patients in this research was from the age range 45-65 years old which is 102 patients (47,7%). The proportion of MTB rifampicin sensitive is 22 patients (10,3%). The proportion of MTB rifampicin resistance is 1 patient (0,05%). And the proportion of MTB not-detected is 191 patients (89,2%). Conclusion: Profile of the result of Genexpert examination in lung tuberculosis patients at Bhayangkara Polda Bengkulu Hospital is sensitive to rifampicin